Motivators of Participation and Non-Participation in Youth Environmental Protests - Feldman, Hannah R. (Frontiers in Political Science, 2021)
This paper is an exploratory study investigating motivators of teenagers to both attend and not attend a climate change related protest event. Using open-ended surveys and focus groups, 16–19-year-old Australian students were asked about their motivators to attend and abstain from School Strike 4 Climate events. Through qualitative analysis and thematic coding, results show key motivators to attend a Strike include climate change and acts of political participation that provide youth with a public voice. Protest is positioned as a key part of teen political repertoires. Reasons for non-attendance included prioritizing schoolwork and low efficacy in protest or participatory action. However, low efficacy in climate change mitigation, or an outright rejection of climate science, was not evident in this sample. Overall, reasons for attendance and non-attendance at a Strike event were not direct mirror images of the other, and implications for inclusion of non-participants in further studies is discussed in this light.